Catholic education in the wake of Vatican II - Bruno-Jofré, Rosa del Carmen, 1946-; Igelmo Zaldívar, Jon, 1982- (University of Toronto Press, 2017)
"The Second Vatican Council (Vatican II), called by Pope John XXIII in 1959, produced sixteen documents that outlined the Church's attempts to meet increasing calls for modernization in the wake of social and cultural changes that were taking place in the twentieth century. Catholic Education in the Wake of Vatican II is the first work dedicated to the effects of the Second Vatican Council on catholic education in various national and cultural contexts. These original pieces, grounded in archival research, explore the social, political, and economic repercussions of Catholic educational changes in Canada, Europe, and South America. The volume provides insightful analysis of many issues including the tensions between Catholicism and Indigenous education in Canada, the secularization of curriculum in the Catholic classroom, Church-State relations and more. The contributors reveal the tensions between doctrinal faith and socio-economic structures of privilege found within the Church and introduces the reader to complex political interactions within the Church itself in the midst of a rapid era of secularization."--